1994
DOI: 10.1007/bf00451347
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry of the breast: Some uncommon cases

Abstract: The incidence of breast asymmetry is not well known. A review of 500 mastoplasties showed that we have treated 26 cases (5.2%) of significant asymmetry. Most of the uneven breasts are rather common cases and can be corrected with routine techniques of reduction and augmentation mammaplasties. In only a few patients is the malformation so pronounced that it requires more elaborate corrective methods. We present six of these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Since each breast arises from an individual anlage (primordium) 4 ' 26 , it is not surprising that one breast bud will appear before its counterpart responds to the hormonal stimulus and BREAST MALFORMATIONS either begin to develop sooner or grow at a more rapid rate 26 . Most individuals remain unaware of it 29 . Most individuals remain unaware of it 29 .…”
Section: Asymmetry Of the Breastsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since each breast arises from an individual anlage (primordium) 4 ' 26 , it is not surprising that one breast bud will appear before its counterpart responds to the hormonal stimulus and BREAST MALFORMATIONS either begin to develop sooner or grow at a more rapid rate 26 . Most individuals remain unaware of it 29 . Most individuals remain unaware of it 29 .…”
Section: Asymmetry Of the Breastsmentioning
confidence: 99%
“…Significant asymmetry of the breasts has been observed in 5.2% of women treated with mammoplasty 29 . Significant asymmetry of the breasts has been observed in 5.2% of women treated with mammoplasty 29 .…”
Section: Asymmetry Of the Breastsmentioning
confidence: 99%
“…Gliosci and Prescutti reviewed their mammaplasty patients and noted significant breast asymmetry in 5.2 percent. 8 However, these data were based on an impression rather than an objective grading scale to assess asymmetry. CONCLUSIONS We have shown that women who receive breast conservation therapy in the treatment of their breast cancer have noticeable treatmentrelated breast asymmetry.…”
Section: Patient Questionnairementioning
confidence: 99%